The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.meegid.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic characterisation, date of divergence, and evolutionary relationships of malaria vectors Anopheles cruzii and Anopheles homunculus

Abstract: The mosquito species Anopheles cruzii and Anopheles homunculus are co-occurring vectors for etiological agents of malaria in southeastern Brazil, a region known to be a major epidemic spot for malaria outside Amazon region. We sought to better understand the biology of these species in order to contribute to future control efforts by (1) improving species identification, which is complicated by the fact that the females are very similar, (2) investigating genetic composition and morphological differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
(59 reference statements)
2
6
0
4
Order By: Relevance
“…The ability of wing traits to capture a genetic pattern so strikingly similar to that inferred from hundreds of molecular loci spread across the 16 honey bee chromosomes [35,52] could be explained by a high heritability and a polygenic nature of wing shape. While the genetic basis of forewing venation is virtually unknown in most insects, including honey bees, it is likely that wing shape has a strong genetic control, as suggested by this and other studies which have also reported concordance between wing morphology and molecular markers, such as mtDNA and microsatellites [78][79][80][81][82][83].…”
Section: Discussionsupporting
confidence: 54%
“…The ability of wing traits to capture a genetic pattern so strikingly similar to that inferred from hundreds of molecular loci spread across the 16 honey bee chromosomes [35,52] could be explained by a high heritability and a polygenic nature of wing shape. While the genetic basis of forewing venation is virtually unknown in most insects, including honey bees, it is likely that wing shape has a strong genetic control, as suggested by this and other studies which have also reported concordance between wing morphology and molecular markers, such as mtDNA and microsatellites [78][79][80][81][82][83].…”
Section: Discussionsupporting
confidence: 54%
“…darlingi from Central America and Colombia. Comparisons of haplotype divergence among Kerteszia species by Lorenz et al (2015) detected a magnitude of difference between An. cruzii and An.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a handful of studies have tried to understand the evolutionary relationship among different species from Kerteszia subgenus (including An. bellator , Anopheles cruzii and Anopheles homunculus ), 6 , 7 rather than investigating the genetic diversity between An. bellator populations.…”
mentioning
confidence: 99%